Resolving water conflicts workbook - De Silva, Lynette; Maser, Chris (Boca Raton, FL : CRC Press, 2022)
This book works to build trust, consensus, and capacity to enhance understanding through a water conflict management framework designed to bolster collaborative skills. Built on case-studies analysis and hands-on real-life applications, it addresses issues of water insecurity of marginalized systems and communities, global water viability, institutional resilience, and the inclusion of faith-based traditions for climate action. The authors assess the complexities of climate challenges and explain how to create sustainable, effective, and efficient water approaches for an improved ecological and socioeconomic future within the UN's Sustainable Development Goals.tive skills. Built on case-studies analysis and hands-on real-life applications, it addresses issues of water insecurity of marginalized systems and communities, global water viability, institutional resilience, and the inclusion of faith-based traditions for climate action. The authors assess the complexities of climate challenges and explain how to create sustainable, effective, and efficient water approaches for an improved ecological and socioeconomic future within the UN's Sustainable Development Goals.
The consequence of a decision and the case of the High Aswan Dam / Chris Maser -- Water conflict transformation / Lynette de Silva -- Evolving water governance under United States law / Holly V. Campbell -- Different systems, common conflicts / Liliana Pimentel and Holly V. Campbell -- Rights of nature : the relationship between water and people / Cameron La Follette -- Intertribal fishing conflicts and federal obstruction in Oregon / David G. Lewis -- The role of women in water management in the Deschutes River Basin of Oregon (USA) and the Ferghana Valley of Central Asia / Jaclyn Best and Jahan Taganova -- Water insecurites in two African-American communities / Lynette de Silva -- A global water solution : an example of the sustainable development goal target 6.5 / Melissa McCracken -- Religious worldviews, environmental values, and conflict-management traditions / Josiah J. Shaver.
OCLC-licensed vendor bibliographic record.
Keywords: Water security; Water rights; Conflict management; Environmental mediation; Water-supply -- Political aspects; LAW / Environmental; POLITICAL SCIENCE / Public Policy / City Planning & Urban Development; TECHNOLOGY / Environmental Engineering & Technology